Medical Institutions And Healing Culture In Central Asia During The Timurid Renaissance (Wire Insights: Journal of Innovation Insights, 2026)
This article examines the development of medical institutions and healing culture in Central Asia during the Timurid Renaissance. The study focuses on the revival of medical knowledge after the period of political and cultural decline caused by the Mongol invasion. It analyzes the role of Timurid rulers in supporting hospitals, pharmacies, physicians, medical education, public hygiene, and ethical principles in medical practice. Particular attention is paid to the activities of Amir Temur, Mirzo Ulugbek, Husayn Bayqara, and Alisher Navoi in creating a favorable environment for the progress of medicine. The article argues that medicine in the Timurid period was not limited to treatment alone, but functioned as an important component of social welfare, scientific development, urban culture, and moral responsibility